Legal Review of Perpetrators of Premeditated Murder Analysis of the Decision in Case Number 474/Pid.B/2023/PN Mdn - Syukurman Jaya Waruwu; Yusuf Hanafi Pasaribu; Winta Hayati (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study examines in-depth the legal analysis of criminal decisions in premeditated murder cases, focusing primarily on Medan District Court Decision No. 474/Pid.B/2023/PN Mdn. The crime of premeditated murder, as regulated by Article 340 of the Criminal Code (KUHP), has the essential element of premeditated intent or intention, which requires the perpetrator to have time to think calmly before committing the act. This crime is considered more serious than ordinary murder because it reflects a high level of criminality and mature malice. The purpose of this study is to critically analyze how the panel of judges constructed their legal reasoning in proving the element of premeditation and assessing the suitability of the decision rendered with the principles of justice and legal certainty.The research method used is normative juridical with a qualitative approach, focusing on applicable legal norms and analysis of court decision documents. Data were obtained through literature review and content analysis of the decisions in the case under study. The results indicate that the panel of judges in this case successfully proved all elements of Article 340 of the Criminal Code convincingly. The judge's considerations were based on a series of legal facts, including digital evidence, consistent testimony, and the results of a post-mortem examination, which detailed the planning and execution of the murder. The sentence handed down to the defendant, which was commensurate with his actions, reflects the implementation of retributive justice and provides a deterrent effect, while also affirming the state's high regard for human life.